Opening up : a grounded theory on how urban indigenous men of Australia respond to cardiovascular disease : a thesis presented in fulfilment of the requirements for the degree of Master of Public Health at Massey University, Wellington, New Zealand - Hoerara, Roy (Massey University, 2013)
Cardiovascular disease is a silent killer which disproportionately affects indigenous communities and families. This research aims to understand how urban Indigenous men of Australia respond, and relate, to cardiovascular disease. The prevalence of heart disease and mortality rate are sixteen times greater for Indigenous aboriginal men aged 25-44 than their non-Aboriginal counterparts. Responses and attitudes toward this disparity are also shaped by the social, economic, and cultural realities which urban Indigenous men of Australia confront on a daily basis. An emergent or grounded theory methodology, informed by an indigenous centred approach was used for this research. Information from twenty in-depth interviews across two community cohorts (New South Wales and Queensland) was gathered, analysed and compared. A number of thematic categories emerged from the data resulting in the observation that urban Indigenous Australian men respond and comprehend cardiovascular disease through the social phenomenon of Opening Up which emerges as both a barrier and a facilitator to improved cardiovascular outcomes. This research has formulated a theory that the relationship between cardiovascular diseases and urban Indigenous males of Australia is a manifestation and consequence of colonisation. This relationship is characterised thematically by four Core Categories of Knowing, Being Indigenous, Being Male and Doing Nothing. The phenomenon observed is one of ‘Opening Up’ which is characterised by three Key Processes of Making Sense, Making Sure and Making Connections. Opening Up is contextualised within a myriad of complex realities. The theory generated by Opening Up is grounded in the data collected and further reinforced by the literature sourced. While not intended to be generalisable, this theory is consistent with this community’s views, needs and expectations. The promotion of Opening Up as a process for consideration is far reaching, perhaps contributing to the Closing the Gaps policy agenda within an Australian public health domain. It may also lend itself to a wider global public health deliberation to better understand the impact of heart disease throughout the world today.
Keywords: Cardiovascular disease (CVD); Aboriginal men; Heart diseases in men; Urban aboriginals; New South Wales; Queensland; Aboriginal health